2022
DOI: 10.1111/ijfs.15608
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and functional properties of albumin, globulin and glutelin fractions of green lentil seed

Abstract: Defatted lentil seed flour proteins were separated into their constituent albumin (ALB), globulin (GLB) and glutelin (GLT) fractions followed by determination of their structural and functional properties. The GLB fraction demonstrated superior solubility (84%-100%) at acidic and alkaline pH values when compared to the lower values for ALB and GLT. Amino acid composition analysis showed lower contents of hydrophobic and sulphur-containing residues for GLB. However, GLB had the highest in vitro protein digestib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…The low distribution of protein in the prolamin fraction (3%) aligns with the findings of Bhatty et al (1976) (3.1% prolamin); the authors remarked that these proteins are likely lowmolecular weight nitrogenous compounds. Interestingly, Osemwota et al (2022) reported that the glutelin fraction was the primary protein class in lentils; however, the fractionation sequence employed was slightly different compared to the present work, as the first extraction media was 2% NaCl and the supernatant was dialyzed against water to obtain the albumin fraction (supernatant) and globulin fraction (precipitate). The saline-insoluble residue was then extracted with 70% ethanol (prolamin fraction), and the ethanolinsoluble residue was extracted with 0.05 M NaOH (glutelin fraction) (Osemwota et al, 2022).…”
Section: Protein Distribution and Extractabilitymentioning
confidence: 85%
See 1 more Smart Citation
“…The low distribution of protein in the prolamin fraction (3%) aligns with the findings of Bhatty et al (1976) (3.1% prolamin); the authors remarked that these proteins are likely lowmolecular weight nitrogenous compounds. Interestingly, Osemwota et al (2022) reported that the glutelin fraction was the primary protein class in lentils; however, the fractionation sequence employed was slightly different compared to the present work, as the first extraction media was 2% NaCl and the supernatant was dialyzed against water to obtain the albumin fraction (supernatant) and globulin fraction (precipitate). The saline-insoluble residue was then extracted with 70% ethanol (prolamin fraction), and the ethanolinsoluble residue was extracted with 0.05 M NaOH (glutelin fraction) (Osemwota et al, 2022).…”
Section: Protein Distribution and Extractabilitymentioning
confidence: 85%
“…The PRO and GLU fractions had no discernable thermal transition, likely due to the low protein content of the PRO fraction and possible denaturation of the GLU fraction due to the highly alkaline extraction pH ($pH 12) (Ma & Harwalkar, 1984). Notably, Osemwota et al (2022) did observe a thermal transition for lentil glutelins, but the transition enthalpy was relatively low compared to the other fractions, which indicates a high degree of denaturation (Arntfield & Murray, 1981). The AE and EE protein extracts exhibited thermal transitions at lower temperatures compared to the Osborne fractions, which could be attributed to partial unfolding of the proteins under alkaline extraction conditions (pH 9.0) (Lee, Htoon, Uthayakumaran, & Paterson, 2007).…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…The two predominant fractions of lentil storage proteins, albumin and globulin, account for approximately 11% and 40% of the total protein content, respectively [Neves & Lourenço, 1995]. The share of glutelins in the protein pool is also significant [Osemwota et al, 2022]. All the essential amino acids were determined in the amino acid profile of the lentil proteins [Liu et al, 2022;Osemwota et al, 2022].…”
Section: Introductionmentioning
confidence: 99%
“…The share of glutelins in the protein pool is also significant [Osemwota et al, 2022]. All the essential amino acids were determined in the amino acid profile of the lentil proteins [Liu et al, 2022;Osemwota et al, 2022]. Their content was balanced well and only the contents of tryptophan and sulfur-containing amino acids (methionine and cysteine) were slightly lower than Food and Agriculture Organization/World Health Organization (FAO/WHO) requirement patterns.…”
Section: Introductionmentioning
confidence: 99%
“…An in‐depth analysis of the physicochemical composition of protein fractions included green lentil seed (Osemwota et al ., 2022), two common bean cultivars (Rossi et al ., 2022) and cowpea used in gluten‐free extruded snacks (HewaNadungodage et al ., 2021). Research related to the modelling of techno‐functional properties, on the contrary, focused on the analysis of the pasteurisation effect on the stability of soybean and peanut membrane proteins (Wu et al ., 2022), the effect of malting and roasting on the functional and nutritional properties of chickpea proteins (Kaur & Prasad, 2022), the influence of the germination process on the functional properties of soybeans and soy milk (Hu et al ., 2021), and the combination of pea proteins with guar gums to improve emulsifying properties.…”
mentioning
confidence: 99%